2023
DOI: 10.1177/16094069231162539
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Recruitment for Qualitative Research: A Comparison of Social Media, Emails, and Offline Methods

Abstract: Participant recruitment through social media platforms has been suggested as an effective method for sampling from specific populations; however, recent online recruitment attempts have been met with varying levels of success. In the current study, we targeted a specific social media population: those who advocate for the Black Lives Matter movement, delineating between those with high and with low follower counts on Twitter. We compared the outcomes of our recruitment methods, which include Facebook ads; unpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…Using technology and social platforms to provide education about research, as well as its benefits and upcoming research opportunities, has not been extensively used in the Hispanic community [37]. The benefits of these platforms includes accessibility, low cost, and rapid transmission throughout a wide community [38,39]. Further, studies have demonstrated that social platforms can be effective when working with hard to reach populations [37,40].…”
Section: Engagement Through Social Mediamentioning
confidence: 99%
“…Using technology and social platforms to provide education about research, as well as its benefits and upcoming research opportunities, has not been extensively used in the Hispanic community [37]. The benefits of these platforms includes accessibility, low cost, and rapid transmission throughout a wide community [38,39]. Further, studies have demonstrated that social platforms can be effective when working with hard to reach populations [37,40].…”
Section: Engagement Through Social Mediamentioning
confidence: 99%